ASPEK-ASPEK KECERDASAN SPRITUAL DAN EMOSIONAL DALAM AL-QURAN (Telaah Surah Luqman Ayat 12-19) - Abu Bakar, Abd Syukur (Inspiratif Pendidikan, 2022)
This journal is written as the author’s sensitivity to the reality of social and moral life that is less humanistic at this time. One way to have a humanist attitude and behavior in the spiritual and emotional side is to study the Koran. This journal raises the formulation of the problem as follows; What aspects of spiritual and emotional intelligence are contained in Surah Luqman verses 12-19? What is the value of spiritual and emotional intelligence education in Surah Luqman verses 12-19? This research is a type of library research using a descriptive-analytical approach. The data collection method in this research is tracing material related to Surah Luqman verses 12-19 and documentation. The data sources used are primary and secondary data sources. The data analysis technique used is descriptive analysis. Descriptive, namely presenting data as realistically as possible according to the research results obtained, then analyzed to reduce the data set through descriptions to obtain conclusions. In this study, there are several aspects contained in the Al-Quran Surah Luqman verses 12-19 which are sourced from 3 interpretations, from the three interpretations, the verse that has aspects of spiritual intelligence is found in the verses 12,13,15,16,17 and the verse which has spiritual intelligence. aspects of emotional intelligence are found in verses 14, 17, 18, and 19. In the Al-Quran Surah Luqman which contains several aspects of spiritual and emotional intelligence and educational values ​​that are building principles of life between God and fellow human beings, namely, starting with of how; being grateful to God’s destiny, uniting God, doing good to both parents, spiritually (conscience), worshiping and doing amar ma’ruf nahi munkar, to how to live socially and ethically. After discussing aspects of spiritual and emotional intelligence along with educational values, it is necessary to make efforts to increase spiritual and emotional intelligence which includes aspects of spiritual intelligence and emotional intelligence in order to place behavior in life through a wider context of meaning. People who have spiritual intelligence usually have concern for others. Like the character Lukman Hakim in Surah Luqman, who teaches his children about commanding ma’ruf nahi munkar. The results showed that Islam has a strong guideline in living a spiritual and emotional life, namely the Koran. Therefore, the Koran needs to be studied in depth, not just reading and listening.